Optimalisasi Pengelolaan Operasional Petshop Berbasis Visual Studio - Fajarwati, Ayu Naila; Rohmah, Nafa Ur Roisatu; Basatha, Rizky (Al-DYAS, 2025)
The increasing demand for efficient and accurate management in petshop operations has highlighted the limitations of traditional methods. This study aims to develop and evaluate a digital solution, "Pet-Tacular," designed to optimize inventory management, transaction processing, and sales reporting using Visual Studio. The application was developed using a VB.NET framework and was tested with a sample of typical petshop operational scenarios, focusing on functionality, user interface simplicity, and real-time inventory accuracy. Data collection involved user testing and feedback, while analysis emphasized system performance and user satisfaction. Results indicate that "Pet-Tacular" significantly enhances operational efficiency by providing real-time stock monitoring, seamless transaction management, and automated report generation. The intuitive interface ensures ease of use, even for users with minimal technical expertise. The findings confirm that the application effectively addresses operational challenges in petshops, contributing to improved service quality and customer satisfaction. This study concludes that integrating technology into petshop operations offers substantial benefits and supports the transition to a more organized, efficient, and competitive business model.